UNDERSTANDING THE NATURE OF METEORITES: THE EXPERIMENTAL WORK OF GABRIEL-AUGUSTE DAUBRÉE - Howarth R.J. (My University, 2006)
The French geologist, mineralogist and experimental petrologist, Gabriel-Auguste Daubrée (1814-1896) was a leading scientist of his generation, possibly best known today for his application of the experimental method to structural geology. During his tenure of the Chair of Geology at the Muséum d'Histoire Naturelle, Paris, to which he was appointed in 1861, he played a leading role in expanding its meteorite collection, developing a classification system for meteorites (1867), and using both petrological (1863-1868) and mechanical (1876-1879) experiments to gain a greater understanding of their chemical composition and how their physical attributes had arisen. This led him to believe in the 'cosmic' importance of peridotites and their hydrated equivalent, 'serpentine' (serpentinite), that the Earth might be unusual in having an oxygen-rich atmosphere and oceans, and that planetary bodies probably had a shell-like structure, increasing in density towards a nickeliferous iron core. (His ideas led to Eduard Seuss's SiA1-SiMa-NiFe model of the Earth.) Following the discovery, by the explorer Nils Nordenskiöld in 1870, of 'native' irons apparently associated with basalts at Disko Island, West Greenland, Daubrée took part in the subsequent investigation and the vigorous debate concerning their terrestrial or meteoritic origin. © The Geological Society of London 2006.